TYPES OF TEACHER’S FEEDBACK USED IN SPEAKING ACTIVITIES AT SECOND GRADES IN JUNIOR HIGH SCHOOLS - David Immanuel Berliando Butar butar; Berlin Sibarani (Universitas Negeri Medan, 2022)
Feedback is one of the most important factors that contribute to students’ success in the learning process. At the same time, teacher feedback is a fascinating topic to discuss. It is important to understand the different types of feedback and why the teacher employed them. This study was conducted to learn about the different types of teacher feedback given by the English teacher of the eighth grade at SMPN 27 MEDAN during the academic year 2022/2023 in speaking activities, as well as the reasons why the teacher gives feedback the way she does. The research design is a descriptive qualitative study based on Stone and Nielsen’s opinions. After analysis, it is clear that the types of teacher feedback stated by the teacher are affective feedback and informative feedback, with informative feedback dominating. Furthermore, the teacher’s motivation for creating them is to improve communication with students and to build a communicative class.